Association of air particulate pollution with bone loss over time and bone fracture risk: analysis of data from two independent studies. Issue 8 (November 2017) - Prada, Diddier; Zhong, Jia; Colicino, Elena; Zanobetti, Antonella; Schwartz, Joel; Dagincourt, Nicholas; Fang, Shona C; Kloog, Itai; Zmuda, Joseph M; Holick, Michael; Herrera, Luis A; Hou, Lifang; et al.
Summary: Background: Air particulate matter is a ubiquitous environmental exposure associated with oxidation, inflammation, and age-related chronic disease. Whether particulate matter is associated with loss of bone mineral density and risk of bone fractures is undetermined. We did two independent studies with complementary designs, objectives, and measures to determine the relationship between ambient concentrations of particulate matter and bone health. Methods: In the first study, we examined the association of long-term concentrations of particulate matter less than 2·5 μm (PM2·5 ) and osteoporosis-related fracture hospital admissions among 9·2 million Medicare enrollees (aged ≥65 years) of the northeast-mid-Atlantic USA between January, 2003, and December, 2010. In the second study, we examined the association of long-term black carbon and PM2·5 concentrations with serum calcium homoeostasis biomarkers (parathyroid hormone, calcium, and 25-hydroxyvitamin [25(OH)D]) and annualised bone mineral density over 8 years (baseline, November, 2002–July, 2005; follow-up, June, 2010–October, 2012) of 692 middle-aged (46·7 years [SD12·3]), low-income men from the Boston Area Community Health/Bone Survey (BACH/Bone study) cohort. PM2·5 concentrations were estimated using spatiotemporal hybrid modelling including Aerosol Optical Depth data, spatial smoothing, and local predictors. Black carbon concentrations were estimated using spatiotemporal land-use regression models. Findings: In the Medicare analysis, risk of bone fracture admissions at osteoporosis-related sites was greater in areas with higher PM2·5 concentrations (risk ratio [RR] 1·041, 95% CI 1·030 to 1·051). This risk was particularly high among low-income communities (RR 1·076, 95% CI 1·052 to 1·100). In the longitudinal BACH/Bone study, baseline black carbon and PM2·5 concentrations were associated with lower serum parathyroid hormone (β=–1·16, 95% CI −1·93 to −0·38, p=0·004, for 1 IQR increase [0·106 μg/m 3 ] in the 1-year average of black carbon concentrations; β=–7·39, 95% CI −14·17 to −0·61, p=0·03, for 1 IQR increase [2·18 μg/m 3 ] in the 1-year average of PM2·5 concentrations). Black carbon concentration was associated with higher bone mineral density loss over time at multiple anatomical sites, including femoral neck (−0·08% per year for 1 IQR increase, 95% CI −0·14 to −0·02) and ultradistal radius (−0·06% per year for 1 IQR increase, −0·12 to −0·01). Black carbon and PM2·5 concentrations were not associated with serum calcium or serum 25(OH)D concentrations. Interpretation: Our results suggest that poor air quality is a modifiable risk factor for bone fractures and osteoporosis, especially in low-income communities. Funding: National Institutes of Health, Institute on Aging, National Institute of Environmental Health, the US Environmental Protection Agency, Consejo Nacional de Ciencia y Tecnología, and the Fundación México en Harvard.